Study of Faraday waves in tanks in presence of polystyrene bead layers - Roux Maxime Christophe Nicolas; Meunier Benjamin Arthur Hugo; Mari Daniele (Emergent Scientist, 2023)
When a tank is subjected to vertical forced excitation, Faraday waves appear at the surface of the liquid the tank contains. In this paper, we consider the effect of layers of polystyrene beads placed on the surface of isopropanol undergoing a low frequency vertical sinusoidal excitation. Beads on the surface remove most of low-frequency resonances and reduce the amplitude of waves for the remaining ones. The formation of resonances with beads is observed to come from small gaps in the bead layers. A sufficient number of beads is needed to maintain beads in one compact block and prevent Faraday waves.